Storage of Pitching Yeast in Brewery - Kopecká, Jana; Kubizniaková, Petra; Fidrich, Lukáš; Matoulková, Dagmar (KVASNY PRUMYSL, 2017)
This article deals with the issue of pitching yeast storage in brewery. The storage conditions before its repitching are a key factor for the quality of the fi nal product. A short overview of factors affecting viability and vitality of yeast during its storage is given, as well as the effect of the way and temperature of its storage on the following fermentation. The stirring of yeast during the storage and acid washing treatment are also discussed.